2009
DOI: 10.3813/aaa.918235
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Subjective Assessment of Water Generated Sounds

Abstract: MEASUREMENT AND SUBJECTIVE ASSESSMENT OF WATER GENERATED SOUNDS ABSTRACTThere is increasing concern with protecting quiet and tranquil areas from intrusive noise. Noise reduction at source and barriers to transmission are mitigation measures often considered. An alternative is to attempt to mask or distract attention away from the noise source. The masking or distracting sound source should be pleasant so that it does not add to any irritation caused by the noise source alone. The laboratory measurements descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 7 publications
(7 reference statements)
5
68
2
Order By: Relevance
“…exposed rock outcrops (Pheasant et al, 2009). The research has been carried out in the laboratory using the playback of video cuts using binaural recordings in a variety of landscapes from open moors through beach scenes and residential areas to city centres.…”
Section: Introductionmentioning
confidence: 99%
“…exposed rock outcrops (Pheasant et al, 2009). The research has been carried out in the laboratory using the playback of video cuts using binaural recordings in a variety of landscapes from open moors through beach scenes and residential areas to city centres.…”
Section: Introductionmentioning
confidence: 99%
“…3 For this purpose, the acoustical properties of water features have been studied by several researchers recently. 4,5 In most cases, it will not be possible to energetically mask the noise from road traffic, even if the water features produce relatively high sound levels. 4,6 On the other hand, introducing sound from water features in the urban environment may still reduce the loudness of road traffic noise 1 due to informational masking effects such as target-masker confusion.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In most cases, it will not be possible to energetically mask the noise from road traffic, even if the water features produce relatively high sound levels. 4,6 On the other hand, introducing sound from water features in the urban environment may still reduce the loudness of road traffic noise 1 due to informational masking effects such as target-masker confusion. 7 However, it is not clear in which situation the addition of sounds also improves the overall soundscape quality.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the water sounds was much less clear as it depressed average ratings by 0.21 scale points. A laboratory study has shown that the quality of the water sound is important and indicated that the water sounds generated from a natural source were more likely to improve tranquility with background traffic noise present [11].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such features are: listed buildings, as these have already undergone a value assessment, religious and historic buildings, landmarks, monuments and man-made elements of the landscape that are geographically and aesthetically in keeping with the natural environment of woods, fields, lakes, hills or parkland. In addition, it was found that the presence of litter and water sounds can decrease or increase ratings, respectively [10,11]. Equation (1) gives the final model [12], where TR = Tranquillity Rating, L Aeq the equivalent continuous sound pressure level of anthropogenic noise and NCF, the percentage of natural and contextual features in the scene (excluding the sky).…”
Section: Introductionmentioning
confidence: 99%